Appropriate use criteria: a review of need, development and applications. (3rd March 2016) - Bhatia, R. Sacha; Alabousi, Mostafa; Dudzinski, David M.; Weiner, Rory B.
ABSTRACT: The costs of healthcare in developed countries have seen a dramatic increase in tandem with the increasing utilization of diagnostic testing. As a result, Appropriate Use Criteria (AUC)-based practices have become more commonplace as a provider-driven solution to reducing unnecessary tests and procedures across various specialty societies. The AUC are meant to serve as a distinct entity from clinical guidelines to help inform clinicians of the 'appropriateness' of a diagnostic test or procedure. In this article, we discuss the development, implementation, impact, and practical applications of AUC to improve appropriate utilization by providers, healthcare institutions, payers, and policy makers. We also focus on the role of education and feedback as a potentially efficacious future method of implementation of global quality improvement and cost-mitigating strategies. AUC represent a growing quality improvement tool in cardiovascular medicine that can play an important role in reducing inappropriate testing while preserving physician autonomy.